2015
DOI: 10.1007/s00441-015-2183-y
|View full text |Cite
|
Sign up to set email alerts
|

miR-124 disinhibits neurite outgrowth in an inflammatory environment

Abstract: Lesions of the central nervous system elicit inflammatory responses that counteract the regeneration of neurites. Microglia and infiltrating macrophages that were activated by trauma have been identified as cellular sources of inhibitory factors. We examine cultured macrophage (RAW264.7) and neuronal (PC12) cell lines to ascertain the potential modulators of the inflammatory impact on neurons. By exposing quiescent macrophages to lipopolysaccharide (LPS) and interferon γ (IFN-γ), cells can be transformed into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…We also found that applying exosomal miR-124-3p to injured neurons, or direct transfection of miR-124-3p into the cells both promoted neurite outgrowth characterized by an increase on the number of neurite branches and total neurite length. These results indicate that microglial exosomal miR-124-3p can promote neurite outgrowth, at least partly by inhibiting neuronal inflammation, which is consistent with the results of a previous report that miR-124-3p disinhibits neurite outgrowth in an inflammatory environment (62). In addition, increased miR-124-3p in microglial exosomes improved the neurologic outcome and inhibited neuroinflammation in rTBI mice.…”
Section: Discussionsupporting
confidence: 91%
“…We also found that applying exosomal miR-124-3p to injured neurons, or direct transfection of miR-124-3p into the cells both promoted neurite outgrowth characterized by an increase on the number of neurite branches and total neurite length. These results indicate that microglial exosomal miR-124-3p can promote neurite outgrowth, at least partly by inhibiting neuronal inflammation, which is consistent with the results of a previous report that miR-124-3p disinhibits neurite outgrowth in an inflammatory environment (62). In addition, increased miR-124-3p in microglial exosomes improved the neurologic outcome and inhibited neuroinflammation in rTBI mice.…”
Section: Discussionsupporting
confidence: 91%
“…In vitro , miR-124 expression is down-regulated by activated microglia, and in the CNS, miR-124 levels correlate inversely with the state of microglial activation and macrophages [ 11 ]. MiR-124 also promotes neuron-microglia interaction and desensitizes neurons in an inflammatory environment [ 51 ]. Increasing miR-124by injection significantly increases neuronal survival and increases number of M2-like polarized microglia/macrophages [ 52 ], and suppresses experimental autoimmune encephalomyelitis symptoms and leukocyte infiltration in the CNS [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages play a vital role in the inflammatory response, but they have also been regarded as a ‘double‐edged sword’ (Okabe & Medzhitov, ). Macrophages can not only promote injured nerve regeneration by clearing debris and inhibiting pro‐inflammatory factors but also provoke excessive inflammatory tissue damage and retard nerve regeneration (Chen et al ., ; Doring et al ., ; Hartmann et al ., ; Kwon et al ., ).…”
Section: Introductionmentioning
confidence: 99%